Survival Analysis of Kidney Failure Patients Using Nelson-Aalen Cumulative Hazard Function Estimation and Log-Rank Test - Safitri, Novita Dwi; Jannah, Salwa Zahrotul (Indonesian Council of Premier Statistical Science, 2025)
Kidney failure is a critical condition that requires intensive monitoring of the patient's survival. This study aims to analyze the survival of kidney failure patients using a survival analysis approach with Nelson-Aalen cumulative hazard function estimation and the Log-Rank Test. The data used consisted of 106 patients with kidney failure who underwent hospitalization for 35 days, with characteristic variables including disease severity (chronic or acute), sex, and age group (≤ 50 years or > 50 years). The results of Nelson-Aalen's estimation showed that patients with acute conditions, male and > age 50 years had a visually higher risk of death. However, the results of the Log-Rank test showed that there was no significant difference in survival function between the three categories (p-value > 0.05). These findings suggest that although there are visual indications of a difference in risk, statistically, these clinical characteristics have not had a significant effect on patient survival in the observation period. This study suggests the need for further studies with data and a broader duration of observations to gain a deeper understanding.